2020
DOI: 10.1016/s1474-4422(20)30272-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related stroke in young individuals

Abstract: eg, if patients are planning pregnancy) and health (eg, if patients have cardiovascular and hepatometa bolic comorbidities). For example, whereas prophylactic treatment could be prescribed in patients with episodic migraine and frequent attacks, acute treatments might be beneficial for patients with a low frequency of attacks. Given the wide variability of antiCGRP and antiCGRP receptor drugs that are now available, with different half lives, the gepants could almost be considered to form a continuum between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 17 publications
8
104
2
6
Order By: Relevance
“…In particular, the formation of microthrombi in multiple organ systems including the lung and the myocardium may result in troponin elevation even in the absence of ST-elevation, making diagnosis challenging. Systemic inflammation along with profound hypercoagulability predisposes to both arterial and venous thrombosis [20] , even without traditional risk factors [21] . Thrombosis increases with worse disease severity and patients with thrombotic events have a significantly elevated risk of all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the formation of microthrombi in multiple organ systems including the lung and the myocardium may result in troponin elevation even in the absence of ST-elevation, making diagnosis challenging. Systemic inflammation along with profound hypercoagulability predisposes to both arterial and venous thrombosis [20] , even without traditional risk factors [21] . Thrombosis increases with worse disease severity and patients with thrombotic events have a significantly elevated risk of all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms in COVID-19 include a hypercoagulable state from systemic inflammation and cytokine storm, postinfectious immune-mediated responses and direct viral-induced endotheliitis or endotheliopathy, potentially leading to angiopathic thrombosis along with cardiomyopathy to name a few. 15 16 One study found 13.5% of patients with COVID-19 had neurological disorder (1.9% of which had stroke), which was associated with an increased risk of in-hospital mortality (HR 1.38, 95% CI 1.17 to 1.62). 17 A recent report of six consecutive patients with acute ischaemic stroke and COVID-19 suggested that all patients had large vessel occlusion with markedly elevated D-dimer levels, often with a period of delay from infection to stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Ischaemic stroke associated with COVID-19 disease occurs in patients of all ages, with more severe strokes, worse functional outcomes and higher mortality rates than are seen in a comparable group of non-COVID-19 patients [148][149][150][151][152]. Thus far, it appears that the major causes for these ischaemic strokes are derived from the hyperinflammatory state and resulting coagulopathy observed in COVID-19 patients, which lead to thromboembolism [153], neurovascular endothelial dysfunction, BBB breakdown, and consequent generalised activation of the CNS innate immune system [149].…”
Section: Cns Effects Of At 2 R Activationmentioning
confidence: 99%